And Yet Software Does Exist (KULT_online, 2009)
Software has received only little attention in media studies and the study of culture. The lexicon Software Studies, edited by Matthew Fuller, addresses this serious shortcoming and investigates the “'stuff’ of software” (p. 1) in altogether 39 entries. Highlighting the manifold interconnections between software, culture, and society, the lexicon not only introduces a new area of research but also calls for further critical investigations.